ANALYSIS OF HERBAR SPECIMENS OF THE GENUS DOREMA DON (APIACEAE LINDL.), KEPT IN THE NATIONAL HERBARIUM OF UZBEKISTAN (TASH) (Scientific journal of the Fergana State University, 2023)
The article analyzed 97 herbarium specimens belonging to the genus Dorema Don, stored in the National Herbarium of Uzbekistan (TASH). As a result of this work, it was established that specimens of 7 species belonging to the genus Dorema are stored in the TASH fund, and the years of collection, collectors and geographical distribution of species were analyzed. GAT maps of the distribution of D. microcarpum and D. sabulosum species found in the flora of Uzbekistan are presented.